2018
DOI: 10.1159/000494022
|View full text |Cite
|
Sign up to set email alerts
|

Patient’s Dietary Beliefs and Behaviours in Inflammatory Bowel Disease

Abstract: Background: The inflammatory bowel disease (IBD) is a chronic lifelong inflammation that may affect the entire gastro-intestinal tract in Crohn’s disease and the colon in ulcerative colitis (UC). Diet plays an important role in IBD patients and many of them follow strict diet restriction in order to reduce complaints and prolong remission intervals. The aim of this study was to assess dietary beliefs, dietary behaviour and nutrition knowledge in Dutch adults with IBD to enable considering the patient’s perspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
92
3
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(114 citation statements)
references
References 21 publications
13
92
3
6
Order By: Relevance
“…In the present study, 55% of participants reported an association between dietary elements and the onset of their IBD symptoms, consistent with the range of 33–68% observed in other studies [ 15 , 17 , 32 , 33 , 34 ]. Moreover, within the range seen in other studies (44–76.5%) [ 32 , 34 , 35 , 36 , 37 , 38 ] a greater percentage of participants (70%) reported an association between diet and symptom exacerbation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, 55% of participants reported an association between dietary elements and the onset of their IBD symptoms, consistent with the range of 33–68% observed in other studies [ 15 , 17 , 32 , 33 , 34 ]. Moreover, within the range seen in other studies (44–76.5%) [ 32 , 34 , 35 , 36 , 37 , 38 ] a greater percentage of participants (70%) reported an association between diet and symptom exacerbation.…”
Section: Discussionsupporting
confidence: 92%
“…The diversity of fruit identified was also less than vegetables, making it difficult to identify a common factor. Citrus fruits have previously been singled out as being problematic [ 32 , 38 , 43 , 48 ], an observation not evident in this study with only one citrus fruit, orange, amongst the most frequently identified fruits. Considering each fruit individually, it is unclear how apple and orange could elicit GI irritation.…”
Section: Discussionmentioning
confidence: 59%
“…Given this scenario, an increasing interest has been given to diet as an easily modifiable environmental factor and, therefore, as a possible preventive or treatment option for IBD [99]. Indeed, IBD patients themselves attribute more importance to diet in affecting their symptoms, than to pharmaceutical treatment [129].…”
Section: Ibd and Dietsmentioning
confidence: 99%
“…Auch wenn Patienten mit IBD großes Interesse an dem Thema Ernährung haben, sind lediglich 8–16% mit den Informationen, die sie von ihren Ärzten erhalten, zufrieden [18]. Interessanterweise konzentrieren sich Patienten in dem Versuch, ihre Ernährungsgewohnheiten zu verändern, eher darauf, bestimmte Nahrungsmittel zu meiden als darauf, ihre Aufnahme von Nahrungsbestandteilen mit wahrscheinlich günstigeren Eigenschaften zu erhöhen [20]. Diese Einstellung ist möglicherweise für Patienten mit IBD wenig hilfreich, sondern führt bei ihnen eher zur eingeschränkten Aufnahme bestimmter Nahrungsmittel mit erheblichen Auswirkungen auf das Sozialleben [17] und zum potenziellen Risiko von Nährstoffdefiziten, u.a.…”
Section: Einführungunclassified